Prevalence of deciduous tooth decay in vulnerable population - Zamarchi, Thiago Gargaro; Tolosa, Vitória Luz; Cassol, Isabel Leticia; Batista, Aline Kruger; Morales, Juliana Maier; Seerig, Lenise Menezes (Disciplinarum Scientia | Saúde, 2024)
The primary objective of this study is to estimate the prevalence of dental caries in primary molars among a vulnerable population in a municipality in the central region of Rio Grande do Sul. This is an observational cross-sectional study in which 49 individuals aged 2 to 12 years were included and assessed through an epidemiological survey using a dental condition assessment form. The prevalence of untreated caries in primary molars in this population was 46.94%, with at least one decayed tooth. Longitudinal studies are needed to determine the cause-and-effect relationship of dental caries in this community. Finally, this study can serve as a basis for formulating effective local public policies and can also provide a framework for research in similar populations.